Utilization of BioMC4 Probiotic Supplementation in Livestock Feed as An Effort to Enhance Animal Health and Productivity in Jombang Regency - Kartika Purnamasari; Andreas Berny Yulianto; Koesnoto Supranianondo (Kontribusia : Research Dissemination for Community Development, 2026)
Probiotics are supplements commonly referred to as “beneficial bacteria” and are widely recognized for their positive effects on health. Over the past decade, probiotics have been increasingly utilized in livestock production, either as single supplements or as feed additives. Probiotic supplementation has been shown to improve digestive processes and nutrient absorption, thereby ensuring adequate nutrient availability for livestock. These benefits are particularly valuable in efforts to improve animal health and production efficiency, especially amid the increasing incidence of Foot and Mouth Disease (FMD) and Lumpy Skin Disease (LSD) in Indonesia in recent years. This community service program targeted a Livestock Farmer Group in Pulosari Village, Bareng District, Jombang Regency. A total of 21 participants actively took part in agricultural extension activities and technical training on silage production using BioMC4 probiotic supplementation. The results of the program indicated that the activity successfully enhanced farmers’ knowledge and practical skills, particularly in relation to the preparation of feed reserves. As a follow-up measure, the community service team established a WhatsApp group with representatives of the farmers to serve as a platform for communication and ongoing technical assistance. In addition, the BioMC4 product was also distributed to all participants so that it could be immediately implemented in their respective livestock facilities. Furthermore, this community service activity is expected to become a sustainable program and provide long-term benefits by reducing production costs associated with maintaining livestock health, improving farmers’ welfare, and strengthening the resilience of the smallholder livestock sector in Jombang Regency.